2020
DOI: 10.3389/fonc.2020.01586
|View full text |Cite
|
Sign up to set email alerts
|

Management of Lateral Multiple-Level Metastasis in N1b Papillary Thyroid Microcarcinoma

Abstract: Background: The optimal extent of therapeutic lateral neck dissection (LND) in the management of N1b papillary thyroid microcarcinoma (PTMC) is still under debate in clinical practice. In this light, our study aims to explore the incidence, patterns, and predictive factors of the lateral multiple-level metastasis in N1b PTMC patients. Methods: The clinical records of 142 patients diagnosed with N1b PTMC who underwent therapeutic LND from July 2015 to November 2018 at our inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…SND refers to dissection of the lateral LNs, sparing ≥1 of the lateral neck levels. SND may be accompanied by a high local recurrence rate (9,10), and MRND can result in a certain degree of shoulder dysfunction and sensory changes (6,11), caused by dissection, traction, or transection of the nerve, which impairs the patient's quality of life (12). The main goal of the clinical management of PTMC is to prevent disease recurrence, reduce patient deaths, and minimize treatmentrelated adverse events.…”
Section: Original Articlementioning
confidence: 99%
“…SND refers to dissection of the lateral LNs, sparing ≥1 of the lateral neck levels. SND may be accompanied by a high local recurrence rate (9,10), and MRND can result in a certain degree of shoulder dysfunction and sensory changes (6,11), caused by dissection, traction, or transection of the nerve, which impairs the patient's quality of life (12). The main goal of the clinical management of PTMC is to prevent disease recurrence, reduce patient deaths, and minimize treatmentrelated adverse events.…”
Section: Original Articlementioning
confidence: 99%
“…However, the incidence and recurrence rate of PTC is gradually increasing throughout the world [ 2 , 3 ]. Further, it has been reported that 66.7% of recurrence incidences of PTC occurred between 5 and 10 years after operation [ 4 , 5 ]. Notably, when recurrence and distant metastasis occur, the treatment of PTC is usually more compliable and difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Papillary thyroid carcinoma (PTC) was the most frequent histological subtype of thyroid malignancy which has a rapidly rising incidence worldwide in the last few decades (1,2). In total, 20.7-62% of patients with PTC present cervical lymph node metastasis (LNM) at initial diagnosis, which was associated with a poor prognosis (3,4), yet the recently updated 8th edition of the TNM staging system eliminates the difference between central (N1a) and lateral (N1b) LNM, and N1b disease is not adopted for the final staging classification (5)(6)(7). These changes have been questioned, and concern arises in such a way that ignoring the metastatic lymph node sites may underestimate recurrence and mortality in patients with PTC.…”
Section: Introductionmentioning
confidence: 99%